Anthocyanins: a promising source of natural colorants and nutraceuticals - Laxmikarthika V. Srinivasan; Sandeep Singh Rana (Discover Applied Sciences)
Abstract Fruits, vegetables, and flowers acquire their diverse pink, red, purple, and blue colors from the presence of polyphenol chemicals called anthocyanins. Additionally, anthocyanins are important for plants' ecophysiology, propagation, and defense mechanisms. Sugars and acyl acids alter the structural makeup of anthocyanidin, resulting in anthocyanins. Light, pH, metal ions, and temperature can all affect anthocyanidin color. Intra- and intermolecular complexations are among the mechanisms that control anthocyanin stability. Anthocyanins have been extracted, isolated, and identified using various spectroscopic and chromatographic techniques. The pharmaceutical, nutraceutical, food coloring, flavoring, and preservation sectors are among those that make substantial use of anthocyanins. Research on complementary commodities and natural, sustainable colors is lacking in these areas. The primary cause of this delay is the labile nature of anthocyanins in different formulations. There are opportunities to modify anthocyanin structures in vivo using cutting-edge gene editing and semi-synthetic techniques. This review covers anthocyanins' structural variations, stability, colors, biogenetics, their functions in human health and welfare, and potential future research areas.